2013
DOI: 10.1103/physrevlett.111.213201
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence on the Mechanism of Dissociative Electron Attachment to Formic Acid

Abstract: Two mechanisms for dissociative electron attachment in HCOOH, the formation of HCOO À þ H, were proposed in the literature: (i) via a direct electron attachment into a à resonance, augmented by dipole binding of the incident electron [G. A. Gallup et al., Phys. Rev. A 79, 042701 (2009)], and (ii) with the 1.8 eV à resonance as a doorway state, linked to the products by symmetry lowering-distortion of the temporary anion, primarily the C-H bond, from the planar symmetry [T. N. Rescigno et al., Phys. Rev. Lett. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 40 publications
(53 reference statements)
3
52
0
Order By: Relevance
“…It is obtained as a combination or the error of the present relative measurements (± 15%) and of the error of the absolute cross sections used for normalization. The latter is taken as ± 15% in view of the results from various groups listed in [20]. The electron-beam resolution in the current experiment is approximately 200 meV.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is obtained as a combination or the error of the present relative measurements (± 15%) and of the error of the absolute cross sections used for normalization. The latter is taken as ± 15% in view of the results from various groups listed in [20]. The electron-beam resolution in the current experiment is approximately 200 meV.…”
Section: Methodsmentioning
confidence: 99%
“…The shape of the O − peak is also used to determine the energy resolution of the electron beam as described in [18]. The absolute cross sections are calibrated using two independent reference values: the O − from CO 2 [19] and HCOO − from HCOOH [20]. The uncertainty of the obtained cross sections is ±20% (two standard deviations).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acetic acid and formic acid have been studied by DEA experiments [22][23][24] where the main focus was given on the dehydrogenated parent anion formation. Meanwhile, DEA theoretical calculations of Rescigno et al [25] have shown that upon electron capture, formic acid proceeds through a π* C=O resonance leading to OH excision.…”
Section: Resultsmentioning
confidence: 99%
“…In spite of the DR2013 success of this approach, particularly in description of VFRs, and in spite of the excellent agreement with experiments on formic acid [27], several objections were made with regard to the existence of the * resonance in these systems. Indeed the standard Breit-Wigner parametrization of the scattering eigenphases did not allow for detection of a low-energy * resonance in formic acid [28], uracil [29][30][31] or glycine [32].…”
Section: Mechanismsmentioning
confidence: 99%